Antidepressivos modificam a extinção de uma memória aversiva em ratas - Melo, Thieza Graziella Araújo da Silva Góes de (2011)
Treatment of major depression, posttraumatic stress disorder and other psychopathologies with antidepressants can be associated with improvement of the cognitive deficits related to these disorders. Although the mechanisms of these effects are not completely elucidated, alterations in extinction of aversive memories are believed to be present in these psychopathologies. Moreover, researches with laboratory animals usually focus on male subjects, and we have recently verified that extinction of an aversive task is reduced in female rats when compared to males. In the present study, female rats were long-term treated with clinically used antidepressants (fluoxetine, nortriptyline or mirtazapine) and tested in the plus-maze discriminative avoidance and forced swimming tests in order to evaluate learning, memory, extinction, anxiety and depression-related behaviors. All groups learned the task, but learning was somewhat faster in nortriptyline and mirtazapine-treated animals . Task retrieval was also showed by all experimental groups. Chronic treatment with fluoxetine, but not with the other antidepressants, increased extinction of the discriminative task. In the forced swimming test, animals treated with fluoxetine and mirtazapine showed decreased immobility duration. In conclusion, antidepressants interfere with learning and female rats treated with fluoxetine presented increased extinction of the aversive memory task. On the other hand, both fluoxetine and mirtazapine were effective in the forced swimming test, suggesting dissociation between the antidepressant effects and the extinction of aversive memories